PERBANDINGAN KEMAMPUAN TEKS ANEKDOT ANTARA YANG MENGGUNAKAN MEDIA GAMBAR KARIKATUR DENGAN MENGGUNAKAN MEDIA GAMBAR MEME SISWA KELAS X SMAN 1 KOTA BENGKULU - Luciana Lidya Sari (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2018)
The purpose of this study to know the difference between the ability to write anecdotal text between the use of caricature drawing media using the meme media of students of class X SMAN 1 Bengkulu City. Methode of studi is kausal comparative. The data of this research is the result of writing ability of anecdot text of students of class X IPA 1 and X IPA 2 SMAN 1 Kota Bengkulu. Data were collected through an anecdotal student writing capability test written on a validated worksheet by the validator. Steps of data analysis: stage 1) performing the scoring, phase 2) performing the test analysis of the press, and stage 3) perform the hypothesis test. From the analysis results obtained the ability to write anecdotal text using caricature drawing media students of class X SMAN 1 Bengkulu City categorized well. This is seen from the average student score is an average score of 83,91. The ability to write anecdotal text using the medium of meme image of grade X SMAN1 students of Bengkulu City is categorized well. This dilaht from the average student score is an average score of 82,34. After t-test, it is found that there is significant difference between experiment group 1 and experiment group 2, that is t count 0,71 and t table 1,669 which means that t count > t table with level of trust 0,05, hence H0 accepted meaning That there is a significant not difference in the ability to write anecdotal text between using caricature drawing media by using the medium of meme image of grade X of SMAN 1 Bengkulu.Keywords: Writing, anecdotal text, caricature, meme